2010
DOI: 10.1128/iai.00106-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofInVitroHIV-1 Infection on Mycobacterial Growth in Peripheral Blood Monocyte-Derived Macrophages

Abstract: Coinfection with human immunodeficiency virus type 1 (HIV-1) and opportunistic mycobacteria, especially Mycobacterium tuberculosis, is a cause of high morbidity and mortality worldwide. Both mycobacteria and HIV-1 may infect macrophages, and thus, coinfection may generate conditions that reciprocally influence the intracellular replication of the pathogens. Elucidation of the interaction between HIV-1 and mycobacteria in their common target cell is important for understanding pathogenesis in coinfected individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 31 publications
3
40
0
1
Order By: Relevance
“…For differentiation into monocyte-derived macrophages (MDM), PBMCs were cultured in RPMI 1640 supplemented with glutamine and 20% pooled heat-inactivated human serum (HS) for 5 days, followed by washing and further maturation for 2 more days in RPMI/10% HS as previously described [6].…”
Section: Methodsmentioning
confidence: 99%
“…For differentiation into monocyte-derived macrophages (MDM), PBMCs were cultured in RPMI 1640 supplemented with glutamine and 20% pooled heat-inactivated human serum (HS) for 5 days, followed by washing and further maturation for 2 more days in RPMI/10% HS as previously described [6].…”
Section: Methodsmentioning
confidence: 99%
“…HIV also leads to a reduction in ex vivo peripheral [6, 7] and airway [8, 9] T-cell cytokine production following M. tuberculosis antigen stimulation. HIV infection has also been shown in vitro to increase the growth of M. tuberculosis in coinfected macrophages [10, 11], but such responses are highly variable [12]. Although these studies demonstrate that HIV causes specific reductions in the immunological responses to M. tuberculosis , very few studies have clearly demonstrated how HIV changes these responses within granulomas [13], the archetypal microscopic hallmark of tuberculosis-diseased tissue.…”
mentioning
confidence: 99%
“…Внутриклеточное инфицирование Mycobacterium tuberculosis вызывает апоптоз мак-рофагов, а также способствует их повреждению с участием Т-хелперов 1-го типа (CD4+), что ограничивает развитие туберкулезной инфекции. В условиях ВИЧ-инфекции, с одной стороны, на-растающий дефицит СD4+ Т-клеток препятст-вует элиминации инфицированных макрофагов, а с другой стороны, создает условия для одновре-менной атаки этих клеток двумя возбудителя-ми -ВИЧ и Mycobacterium tuberculosis [62,63]. ВИЧ не оказывает цитопатического воздействия на макрофаг, но приводит к метаболическим на-рушениям, следствием которых является подав-ление синтеза ИЛ-10 -цитокина, контролиру-ющего развитие воспалительной реакции.…”
Section: провирус вгч-8unclassified